2017
DOI: 10.4236/ojss.2017.711023
|View full text |Cite
|
Sign up to set email alerts
|

Functional Diversity of Mycorrhizal Fungi Has Differential Effects on Salinity Tolerance of <i>Acacia seyal</i> (Del.) Seedlings

Abstract: Acacia seyal is a leguminous plant that plays an important role in the ecosystem of Sahelian zone by producing gum, wood and fodder. The growth of A. seyal is subject to many constraints as salinity which can affect the development of this tree. Therefore, soil microorganisms can help A. seyal to better tolerate the effects of negative environmental stresses. The contribution of arbuscular mycorrhizal fungi (AMF) to the salt tolerance of A. seyal, was evaluated by testing the effects of eight different arbuscu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 51 publications
2
4
0
Order By: Relevance
“…Even though not significant, it was also relatively higher around the tree bole than an open area. is might be due to the microbial association and low leaching problems of base-forming cations around a tree [53]. e result agreed with Kassa et al [50] and Wolle et al [45] who reported nonsignificant effects of Balanites aegyptiaca and Ziziphus spina-christi over EC at the arid areas of Humera and Hibru districts of Ethiopia, respectively.…”
Section: Effect Of Acacia Seyal On Soil Propertiessupporting
confidence: 85%
“…Even though not significant, it was also relatively higher around the tree bole than an open area. is might be due to the microbial association and low leaching problems of base-forming cations around a tree [53]. e result agreed with Kassa et al [50] and Wolle et al [45] who reported nonsignificant effects of Balanites aegyptiaca and Ziziphus spina-christi over EC at the arid areas of Humera and Hibru districts of Ethiopia, respectively.…”
Section: Effect Of Acacia Seyal On Soil Propertiessupporting
confidence: 85%
“…At the same time, an abundance of Acacia seyal seeds germinated in one rainy season and has better survival potential than other species, which allows for better colonization [48]. Its association with microorganisms such as arbuscular mycorrhizal fungi (AMF) is also reported to be related to its better survival potential even in harsh conditions, because associated microorganisms encourage it for fast growth of shoot and root biomass, improve nutrient taking, and promote its mycorrhizal symbionts [49]. Besides this, as farmers in southeast Ethiopia acknowledged, seed dispersal means like browsing animals, vehicles, food, and wind contributing to its colonization in large areas in a short period of time [18].…”
Section: Acacia Seyal and Its Growthmentioning
confidence: 99%
“…Mycorrhization facilitates the adaptation to saline conditions by helping plants procure soil nutrients, particularly magnesium, during the growth cycle (Giri and Mukerji, 2004). Nevertheless, the ability of an AMF strain to enhance plant growth and development is not directly correlated to whether or not it originates from a saline area (Cantrell and Linderman, 2001;Manga et al, 2017). Thus, the fact that plant growth promotion occurs suggests that this trait is a characteristic of the individual isolate's ecotype, and is not directly related to salt.…”
Section: Effect Of S Senegal On Soil Fertilitymentioning
confidence: 99%